2013
DOI: 10.1080/10410236.2013.789131
|View full text |Cite
|
Sign up to set email alerts
|

See the Seal? Understanding Restrained Eaters’ Responses to Nutritional Messages on Food Packaging

Abstract: Food packaging in general and packaging incorporating health messages in particular have been active areas of inquiry, receiving attention from policymakers and food manufacturers alike. This study explores the effects of package seals and claims on perceived product healthfulness as a function of dietary restraint status. A laboratory experiment using realistic three-dimensional packaging shows that for restrained eaters (i.e., those who try to restrict their food intake), nutrition claims on "healthy" produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…However, the amount eaten was not affected by these labels, so the data do not replicate Provencher, Polivy, and Herman's [10] finding that healthy labels led restrained eaters to eat more cookies. A later study replicated the effects of package labels and nutritional claims on the perceived healthfulness of the food for restrained eaters but not unrestrained eaters (although food intake was not measured) [11]. Similarly, giving brand and caloric/energy information affected how the cookies tasted to both restrained and unrestrained eaters [12], but restrained eaters ate more cookies from the healthy than the unhealthy brand unless the unhealthy ones were said to have fewer calories (lower energy density), in which case restrained eaters increased their consumption of those.…”
Section: Health-related Food Cuesmentioning
confidence: 94%
“…However, the amount eaten was not affected by these labels, so the data do not replicate Provencher, Polivy, and Herman's [10] finding that healthy labels led restrained eaters to eat more cookies. A later study replicated the effects of package labels and nutritional claims on the perceived healthfulness of the food for restrained eaters but not unrestrained eaters (although food intake was not measured) [11]. Similarly, giving brand and caloric/energy information affected how the cookies tasted to both restrained and unrestrained eaters [12], but restrained eaters ate more cookies from the healthy than the unhealthy brand unless the unhealthy ones were said to have fewer calories (lower energy density), in which case restrained eaters increased their consumption of those.…”
Section: Health-related Food Cuesmentioning
confidence: 94%
“…However, after running such analyses, no remarkable differences in the data were observed suggesting that such contrast in consumption habits triggered robust differences across the obtained results (cf. Lwin et al, 2014). Such null effects may also be related to the split of the sample and, hence, a consequent underpowered analysis.…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…Concerning verbal typologies, several studies have verified how particular sensory aspects of products, which may also be related to healthiness, can be influenced by messages present on food/beverage packaging (e.g., Tuorilla and Cardello, 2002;Verbeke et al, 2009;Carrillo et al, 2012;Lwin et al, 2014;Miraballes et al, 2014;Pinto et al, 2017;Steinhauser and Hamm, 2018;Steinhauser et al, 2019). Carrillo et al (2012), for instance, studied consumers' perceptions of low-calorie cookies packaging, alternating tasting/non-tasting sessions with presence vs. absence of information on packaging.…”
Section: Verbal Typologies In Packagingmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed below, this reveals the field to be multidisciplinary and relates the importance of packaging to several specific themes. In the cluster -diet‖, Lwin et al (2013) explored the effects of package labelling that identifies the health risks of consuming certain foods and indicated that nutrition labels have little effect on people who eat wantonly. And in the cluster -FSANZ‖, an article by Williams et al (2003) aimed to describe the use of nutrition information on packaging and measured how this information followed regulatory standards.…”
Section: Figure 5 Network Between Countriesmentioning
confidence: 99%